Creditors Attitude towards Clients Sustainability Reporting Practices in India - Venugopal, Bandaru (Asian Business Review, 2019)
The research is aimed at “To evolve a method of sustainability reporting practices for social expenditure incurred by business organizations so that the information to the creditor and stakeholders becomes “impact measurable” thereby, becomes more meaningful & relevant.”Since sustainability reporting practices are getting more & more adopted by many companies there is a great need to come out with an appropriate method for reporting which may cover quantitative & qualitative aspects & also measure the impact of such contribution. In contrast to financial reporting,  the history of sustainability reporting  (SR)  is comparatively recent.  The proposition that organizations,  and business organizations  in particular,  should supplement their financial accounting with accounting on their environmental,  social and other  'non-financial'  performance  -  or  'sustainability reporting'. Responding to the increasing media attention to environmental problems, most reports focused on environmental policies and performance. This present research paper attempts to evaluate the Creditors' participation in framing sustainability reporting practices in India. Result Mean weighted score towards awareness on sustainable reporting practices (SRP) of their clients is 3.71, i.e.74.2 percent level of awareness that provides satisfaction on their client’s repayment terms to the extent of 3.10 score or 62 percent only. Therefore, it can be concluded that the impact of sustainable reporting practices of SENSEX companies on their creditors’ terms is significant statistically. Hence, it is suggested to the creditors to examine the variables (such as ASRP, PSA, and SDI) which have a negative impact on the creditors and further it should improve the variables (CEPCD, CSSR, G, AG & Q) which have a positive impact but not significant statistically.